Viewing Salary And Workload As An Influence On Job Satisfaction Of PT. JNE Express Ambon Branch Nugraha Ekakurir Route Employees - Felix Chandra (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
This study aims to investigate the effect of salary and workload on employee job satisfaction at JNE. This study used a sample of 35 employees determined through the Simple Random Sampling technique and based on the Slovin formula, and applied validity, reliability, and classical assumption tests to ensure the validity of the data. Multiple regression analysis is a statistical test conducted to determine the extent of the influence of independent variables on the dependent variables studied. Data calculations and influences use SPSS as a data analysis tool. The results of the study indicate that salary has a positive and significant effect on job satisfaction, and workload also has a positive and significant effect on job satisfaction.